Investigating the association between COL1A1 and COL3A1 gene variants and knee joint laxity and ligament measurements. (December 2022) - Beckley, Samantha; Dey, Roopam; Stinton, Shaun; van der Merwe, Willem; Branch, Thomas; September, Alison V.; Posthumus, Mike; Collins, Malcolm
Abstract: Background: Joint laxity is a multifactorial phenotype with a heritable component. Type I collagen gene (COL1A1 ) mutations cause connective tissue disorders with joint hypermobility as a clinical feature, while variants within COL1A1 and type III collagen gene ( COL3A1 ) are associated with musculoskeletal injuries. The aim of this study was to investigate whether COL1A1 and COL3A1 variants are associated with measurements of non-dominant knee joint laxity and computed ligament length changes. Methods: 106 moderately active uninjured participants were assessed for genu recurvatum, anterior-posterior tibial translation, external-internal tibial rotation and calculated ligament length changes during knee rotation. Participants were genotyped for COL1A1 rs1107946, rs1800012 and COL3A1 rs1800255. Findings: The COL1A1 rs1107946 GG genotype had significantly larger external rotation [GG: 5.7° (4.9°;6.4°) vs GT: 4.6° (4.2°;5.5°), adjusted P  = 0.014], internal rotation [GG: 5.9° (5.3°;6.6°) vs GT: 5.4° (4.7°;6.2°), adjusted P = 0.014], and slack [GG: 18.2° ± 3.2° vs GT: 16.1° ± 3.1°, adjusted P = 0.014]. The GG genotype at both COL1A1 variants had significantly larger active displacement [GG + GG: 6.0 mm (3.8 mm;8.0 mm) vs other genotype combinations: 4.0 mm (2.5 mm;6.0 mm), P  < 0.001] and maximum displacement [GG + GG: 8.0 mm (6.9 mm;10.6 mm) vs other genotype combinations: 6.0 mm (5.0 mm;9.0 mm), P  = 0.003]. COL1A1 rs1107946 significantly contributed to increased external and internal rotation in multilinear regression models, while both COL1A1 variants, significantly contributed to increased active displacement and slack. Larger medial and lateral cruciate ligament length changes were reported in participants with GG genotypes at both COL1A1 variants. Interpretation: These findings suggest that the COL1A1 variants are associated with knee rotational laxity and changes in ligament length. Highlights: Type 1 Collagen gene ( COL1A1 ) variants are associated with knee rotational laxity. COL1A1 variants are associated with maximum and active tibial displacement. They also associate with changes in medial and lateral cruciate ligament length. These variants contribute to knee joint laxity in multilinear regression models.